Two new species and additional records of Domene from China and Vietnam (Coleoptera: Staphylinidae: Paederinae). - Assing, Volker (Contributions to Entomology = Beiträge zur Entomologie, 2016)
Two species of Domene Fauvel, 1873 from China are described and illustrated: Domene (Macromene) contiger spec. nov. (Guangxi) and D. (M.) exicta spec. nov. (Hubei). Additional records of three species are reported from China (Hebei, Hubei, Shaanxi, Sichuan) and North Vietnam. Including the new species, Domene now includes 67 named species, 16 of which have been recorded from China, two from Taiwan, and two from Vietnam. Keywords Coleoptera, Staphylinidae, Paederinae, Lathrobiina, Domene, Palaearctic region, China, Vietnam, taxonomy, new species, additional records. Nomenclatural Acts contiger Assing, 2016 (Domene (Macromene)), spec. n. exicta Assing, 2016 (Domene (Macromene)), spec. n.